Analysis of inertial measurement accuracy using complementary filter for MPU6050 sensor - Mohd Sultan, Juwita; Zani, Nurul Huda; Mohd Azuani; Siti Zuraidah, Ibrahim; Azdiana, Md Yusop (Penerbit Universiti Kebangsaan Malaysia, 2022)
Inertial can be defined as disinclination to motion, action, or change. The inertia of an object is the propensity to remain at rest or if in motion, stays in motion at a steady speed. MPU6050 is one of the low-cost motion tracking sensors that contain a 3-axis gyroscope and 3-axis accelerometer orientation measurement. It is used to analyse the movement or location of a person in an indoor environment. This research is to analyse the accuracy of the inertial measurement of the MPU 6050 sensor. Next, is to improve the achievable accuracy rate up to 95% using the complementary filter and finally to visualize the results on an IoT platform. This MPU6050 sensor is beneficial to an emergency responder such as the firefighter’s department. The accurate inertial measurement and location will help to detect the movement and the motion of the firefighter during operation, especially in an indoor environment. The sensor will detect and collects the inertial measurement of an emergency responder and transmit the data wirelessly by using ESP8266 NodeMCU. Finally, the results can be viewed on an IoT platform. However, the results obtained from the MPU 6050 sensor is not perfectly accurate as there is noise during the measurement. Therefore, a complementary filter is used and analysed in this research. It is expected that the inertial location’s accuracy could be improved by 95% that will provide a precise movement and location of the firefighter during operation.